AKUT PUROMYCİNE AMİNONUCLEOSİDE NEFROZDA PROTEİNÜRİ, KREATİNİN KLİRENSİ, SERUM ALBUMİN DEĞERLERİ İLE BÖBREK CİSİMCİĞİNDEKİ ULTRASTRÜKTÜREL DEĞİŞİKLİKLER VE SLİT-PORE SAYISI ARASINDAKİ İLİŞKİLER - Seçkin, İsmail; Uzunalan, Mümin; PEKPAK, Meltem; Köktürk, Sibel; URULUER, Bülent; SÖNMEZ, Hüseyin; ÖZTÜRK, Zeynep; ŞATIROĞLU, Güngör (Cerrahpaşa Medical Journal, 2019)
Background and Design.- We tried to investigate in puromycine aminonucleoside (PAN) Wistar rats, (whom we injected subcutaneously 1.67 mg/100g PAN), the relationship of clinical proteinuria and morphological changes. In our groups ‘before clinically established proteinuria’ and after developed ‘acute nephrosis’, ultrastructural changes of the corpusculum renale Malpighi, morphologically alterations of the number of the slit-pores during developing proteinuria and the hydraulic permeability changes were correlated with the clinical parameters. Result.- In the group with not yet established proteinuria podocytes were hypertrophied. The glomerular basement membrane was invaginated into the foot processes and thickened. Slit pore count was decreased in comparison to control rats (control: 32.68± 0.6, ‘before proteinuria’: 16.3±1.11). In the fused foot processes, which formed foot processes with an enlarged cytoplasma, we could see highly condensated microfilaments near the glomerular basement membrane. In the ‘acute nephrosis’ group the slit-pores count were even more decreased (6.05±1.54). In the rats which showed lesser proteinuria than others, in the acute group, protein absorption granules (PAG) and the different stages of PAG formation and secretion from podocyte were observed. In the rats with lower proteinuria we observed hypertrophy, increased endocytic activity, fused foot processes condensate electron dense microfilaments and PAG in the podocytes. Mesangial cells were increased. In the rats with high proteinuria, podocytic PAG and microfilaments were decreased and pseudocysts appeared. In the Cavum Bowmani, free apoptotic podocytes were to be seen. Foot processes slimmed, lengthened, fusion increased and high condensation of microfilaments disappeared. PAG were highly decreased. GBM was generally thinned and often nude GBM was noticed, with totally lost foot processes. In areas of degenerated podocytes, mesangial matriks expansion was attracting our attention. Close proximity to perimesangial area, within the increased mesangial matriks, electron dense deposits were observed. Control group and the group ‘before established proteinuria’ were not significantly different from each other concerning the level of proteinuria, serum albumin and creatinine clearance. In the ‘acute nephrosis’ group proteinuria increased significantly from 5.04±2 to 91.34±91 mg/24 hours, serum albumin and creatinine clearance decreased from 3.23±0.1 to 2.5±0.63 g/dl, from 0.55±0.8 to 0.38±0.28 ml/min respectively. Conclusion.- Our results showed us that in PAN nephrosis: 1-The firstly affected cells are the podocytes 2-There is a relationship between proteinuria, serum albumin and creatinine clearance loss and slit pore decrease 3-The podocytes first endocytose proteins and later with help of intracellular lysosomal activity, break them into pieces, to secrete them by exocytosis and use for all this the intracytoplasmic way 4-Loss of the foot processes or totally nude GBM areas are the real culprit of high levels of proteinuria and apoptosis in podocytes is induced.